SIKAP DAN PERILAKU HUBUNGANSEKSUAL PRANIKAH REMAJA DI INDONESIA (ANALISIS DATA SKRRRI 2007) - , SUPRIYADI, S.PD. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aimed to identify the relationship of perception, information and social environmental factors on the premarital sexual relation attitude and behavior. Perception factors included the perceptions on virginity, marriage, and pregnancy, while information factors consist of discussion concerning reproductive health with family, discussion on reproductive health with peers, knowledge on fertile period, knowledge on HIV/AIDS and mass media exposure on reproductive health. While the social environment factor involve peer social environment, access to reproductive health association, socialization on reproductive health in the community, and reproductive health topics in school. This study exploited the data of the 2007 Indonesian Reproductive Health among Adolescents. The purpose of this research was to statistically analyze factors influencing attitudes and behavior of premarital sexual relations among Indonesian adolescents. The processed data involved all respondents in the survey of adolescent reproductive health, totaling 19,311 Indonesian adolescents. The chi-square (Ï Â²) and logistic regression statistical tests were used in this research. The trends (opportunities) and relationship path were viewed from the odds ratio (OR) with confidence intervals (CI) of 95 percent (p-value <0.05) and pathway analysis. The multivariable analysis results showed that several variables showed consistent influences on sexual attitude and behavior among Indonesian adolescents. These variables involved the perceptions on virginity, marriage, and pregnancy, discussion with family, discussion with peers, peer environment, and reproductive health topics in school. The six variables showed direct and indirect relations on the premarital sexual relation behavior with variable attitude on premarital sexual behavior. The variable reproductive health socialization in the community merely provided significant effects to attitude on premarital sexual relations, while knowledge on fertility, media exposure merely had significant influences on premarital sexual relation behavior. The study also found that advances in technology and information that is marked by the number of adolescents who access the mass media, especially television that includes reproductive health messages, it contributes significantly less on the premarital sexual relation attitude and behavior. Similarly, the increasing influence of peers would have a negative impact on the premarital sexual relation attitude and behavior among adolescents. The value of virginity which is reflected by avoid premarital sexual intercourse, discussions with family and reproductive health topics can give a positive effect on the premarital sexual relation attitude and behavior among adolescents.